PENERAPAN DASA DHARMA PRAMUKA BUTIR KE DELAPAN (DISIPLIN, BERANI DAN SETIA) DALAM MEMBENTUK KARAKTER MAHASISWA MELALUI PENDIDIKAN KEPRAMUKAAN - Maulana Ahmad Syifa; Muhammad Hanief; Fita Mustafida (VICRATINA, 2019)
This research is an attempt to find out the application of Dasa Dharma scout item eight (discipline, courage and loyalty) in shaping the character of students through scouting education (Study at the UKM Racana Scout Movement KH Oesman Mansoer and Nyai Khoiriyah Hasyim Islamic University Base Malang). Whereas the UKM Scout Movement is one of the student activity units engaged in scouting as a place for students who like to participate in activities for training and self-development, both in the fields of scouting, mentality, character and in life in society. The Eighth Dasa Dharma is disciplined, courageous and loyal. Character formation is carried out every activity in the UKM Scout Movement by using methods that are interesting, challenging, educational and fun will make someone not feel bored and bored in learning